Salariaţii români – câştigători şi perdanţi ai tranziţiei - Preotesi, Mihnea (Calitatea Vieții, 2006)
After the collapse of communist regimes, the former communist countries, Romania being among them were confronted with substantial increase of inequalities regarding the incomes distribution. The 16 years of transition induced major changes in wage distribution configuration, meaning that the difference increased, fact that had a direct impact on the living standard of salarieds house holds. In today Romania, the salarieds house holds are a very heterogeneous category, regarding income and life style. Within this context, we shall analyse the differentiated effects of some policies with global impact, subordinated to desideratum as macrostability, over some categories of salarieds house holds. We also propose an analysis of the impact of companies policies in the field of salaries, including financial, as well as non financial benefits over the salarieds consumption. In fact, what we intend to do is, in the end, to answer the question: which categories of salaried can be considered as transition loosers, and which can be considered as winner?